Collective action for smallholder market access - Markelova, Helen; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2009)
Issues concerning farmers with small land holdings figure prominently in global discussions about poverty reduction, as the majority of the world's poor belong to such households. Most of these households are linked to the market in one way or another. Thus, the opportunity for smallholders to raise their incomes from agricultural production, natural resource management, and related rural enterprises increasingly depends on their ability to sell their goods not just at local, but also regional and even international markets. Agricultural producers in the developing world face significant challenges as a result of changing economic, environmental, and sociopolitical conditions. Changes in the global agricultural economy are providing smallholders with new opportunities that also present new constraints. The demand for higher value and processed foods as well as the rise of supermarkets around the world has implications for the entire food marketing system as it alters procurement systems and introduces new quality and safety standards. For example, European supermarket chains have imposed stringent food safety requirements such as GLOBALGAP on their suppliers of horticultural products, making it more challenging for farmers to supply these outlets. Smallholders also face significant challenges that hinder their participation in new marketing opportunities. Markets in the developing world are characterized by pervasive imperfections such as lack of information on prices and technologies, high transaction costs, and credit constraints. Moreover, the new procurement systems often expect larger supply volumes, favoring larger farmers. With the increasing number of free trade agreements affecting both national and international commodity markets, smallholder farmers are forced to compete not only with their local peers, but also with farmers from other countries as well as domestic and international agribusinesses. There is increasing evidence from both research and practice that one way for smallholders to overcome market failures and maintain their market position is through organizing into farmer groups or producers organizations. Acting collectively, smallholders would be better positioned to reduce transaction costs for their market exchanges, obtain necessary market information, secure access to new technologies, and tap into high-value markets, allowing them to compete more effectively with large farmers and agribusinesses. Producer groups can simplify long marketing chains by connecting smallholders directly to markets, bypassing various marketing intermediaries.